Bone Healing Improvements Using Hyaluronic Acid and Hydroxyapatite/Beta-Tricalcium Phosphate in Combination: An Animal Study. (14th December 2016) - Chang, Yen-Lan; Lo, Yi-June; Feng, Sheng-Wei; Huang, Yu-Chih; Tsai, Hsin-Yuan; Lin, Che-Tong; Fan, Kan-Hsin; Huang, Haw-Ming
Abstract : The purpose of this study was to investigate whether the use of HLA as an aqueous binder of hydroxyapatite/beta-tricalcium phosphate (HA- β TCP) particles can reduce the amount of bone graft needed and increase ease of handling in clinical situations. In this study, HA/ β TCP was loaded in commercially available crosslinking HLA to form a novel HLA/HA- β TCP composite. Six New Zealand White rabbits (3.0–3.6 kg) were used as test subjects. Four 6 mm defects were prepared in the parietal bone. The defects were filled with the HLA/HA- β TCP composite as well as HA- β TCP particle alone. New bone formation was analyzed by micro-CT and histomorphometry. Our results indicated that even when the HA- β TCP particle numbers were reduced, the regenerative effect on bone remained when the HLA existed. The bone volume density (BV/TV ratio) of HLA/HA- β TCP samples was 1.7 times larger than that of the control sample at week 2. The new bone increasing ratio (NBIR) of HLA/HA- β TCP samples was 1.78 times higher than the control group at week 2. In conclusion, HA- β TCP powder with HLA contributed to bone healing in rabbit calvarial bone defects. The addition of HLA to bone grafts not only promoted osteoconduction but also improved handling characteristics in clinical situations.